Pengaruh Metode Ekstraksi Terhadap Kandungan Senyawa Polifenol dan Aktivitas Antioksidan pada Rubus fraxinifolius - Yesi Desmiaty; Berna Elya; Fadlina Chany Saputri; Iis Irawatty Dewi; Muhammad Hanafi (Fakultas Farmasi Universitas Pancasila, 2019)
Rubus fraxinifolius can be founded in the mountainous regions of West Java. Previous studies have shown that this plant has potent antioxidant activity. The content of polyphenol compounds in this species contributes substantially to antioxidant activity, and the extraction method will affect the content of the compound. In this study an evaluation of the extraction method effect on leaves, young fruits and stems of R. fraxinifolius on the content of polyphenols and their antioxidant activity, have been done. Method: The leaves, fruits, and stems of R. fraxinifolius were extracted by maceration, reflux, and soxhlet using methanol as a solvent. Each extract was determined the total polyphenol content using Folin-Ciocalteu reagent and antioxidant activity test using DPPH reduction method. Result: The highest extract yield was R. fraxinifolius leaf reflux extract (30.20%). The highest total polyphenol content was given by the Soxhlet extract of leaf R. fraxinifolius (48.79 mg GAE / g extract). The highest antioxidant activity was leaf Soxhlet extract of R. fraxinifolius (98.29% at 100 ppm). Conclusion: From this study it was shown that the methanol extract of R. fraxinifolius leaves extracted by Soxhlet gave the highest polyphenol content and antioxidant activity.